2016
DOI: 10.1590/0037-8682-0156-2016
|View full text |Cite
|
Sign up to set email alerts
|

Screening of the in vitro antileishmanial activities of compounds and secondary metabolites isolated from Maytenus guianensis Klotzsch ex Reissek (Celastraceae) chichuá Amazon

Abstract: Introduction:Maytenus guianensis is a member of the Celastraceae family that is used in traditional medicine, particularly for its anti-parasitic and anti-cancer effects. To explore the ethnopharmacological potential of this plant, the present study was designed to screen the in vitro antileishmanial activities of extracts and compounds isolated from M. guianensis. Methods: Maytenus guianensis stems and leaves were extracted in acetone, followed by the preparation of eluates and isolation of secondary metaboli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
(24 reference statements)
0
7
0
8
Order By: Relevance
“…We separated the hexanic extract by using silica gel column chromatography, and eluted it with n-hexane, followed by a mixture of n-hexane: CHCl 3 , which had greater polarity. Moreover, we determined the structures of all isolated compounds by analyzing their spectral data (IR, MS, 1 H, and 13 C, including COSY, HMQC, HMBC, and NOESY spectra) and comparing them with the existing literature data 3 .…”
Section: Guianensis Bark Was Collected From the Adolpho Duckementioning
confidence: 99%
See 3 more Smart Citations
“…We separated the hexanic extract by using silica gel column chromatography, and eluted it with n-hexane, followed by a mixture of n-hexane: CHCl 3 , which had greater polarity. Moreover, we determined the structures of all isolated compounds by analyzing their spectral data (IR, MS, 1 H, and 13 C, including COSY, HMQC, HMBC, and NOESY spectra) and comparing them with the existing literature data 3 .…”
Section: Guianensis Bark Was Collected From the Adolpho Duckementioning
confidence: 99%
“…To date, no studies have reported the insecticidal activity of tingenone B; however, Meneguetti et al 3 reported that this substance was the most active triterpene of M. guianensis and completely inhibited the growth of Leishmania amazonensis promastigotes at 100 ppm concentration. Interestingly, the lepidopteran larvae Cydia pomonella, fed on a diet containing a similar molecule, 20-α-hydroxytingenone, presented an LC 50 of 13.0 mg/mL (13,000 ppm) after 5 days of feeding 12 ; whereas for A. aegypti, the LC 50 was 15 ppm after 48 h of contact, thereby suggesting that changes in the position of functional groups are related to the insecticidal potential of these triterpenes.…”
Section: Guianensis Bark Was Collected From the Adolpho Duckementioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the following products of the Amazonian biodiversity for diversified products are on the market for cosmetics applications: Babaçu Research in the medical field confirms the value of many indigenous traditional medicines and goes beyond, with its own and advanced research methods [36]. As an example, we can mention the chichuá (Maytenus guianensis Klotzsch ex Reissek) that presents anti-leishmaniosis [37] and anti-microbial [38] compounds; guaraná (Paullinia cupana) with its properties for the treatment of Alzheimer's disease [39], priprioca (Cyperus articulatus L.) with anticonvulsant properties [40], babaçu (Orbignya phalerata) with a cicatrizing compound [41], sacaca (Croton cajucara Benth.) with hypoglycemic properties [42] and as ulcer healing [43], pracaxi (Pentaclethra macroloba Willd.)…”
Section: Potential Of a Biodiversity-based Bio-economymentioning
confidence: 99%